Oral Ketamine. Is it safe? - Joshi, Arbin; Awale, P; Lee, M (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: Safety of use of ketamine by the oral route has not been verified. Methods: Randomized controlled trial involving 30 patients in each group, comparing effects of oral ketamine and intravenous morphine on vital signs and oxygen saturation. Results: Significant change in Systolic blood pressure was noted after administration of oral ketamine (p < 0.05), which normalized after 2 hours of administration of the drug but change in Diastolic blood pressure, Mean Arterial pressure and oxygen saturation was insignificant (p>0.05). Conclusion: Use of Oral Ketamine can be considered a safe method for conscious sedation